Analisis Preferensi dan Kepuasan Penerima Bantuan Pangan Non Tunai (BPNT) terhadap Beras di Kota Denpasar - DEWA AYU INDAH YULANDARI; I WAYAN BUDIASA; I DEWA GEDE RAKA SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Analysis of Preference and Satisfaction of Non-Cash Food Aid Recipients (BPNT)Against Rice in Denpasar City.Income differences are one indicator of differences in social classes. The role ofgovernment is very influential in the lower middle class. The government assistanceprogram in the form of Rastra, is channeled in non-cash by transforming from assistanceto subsidy patterns to social assistance (food). The purpose of this study to determinethe characteristics, preferences and customer satisfaction of rice recipients of Non-CashFood Aid (BPNT) was assessed from the level of importance and level of performanceof the attributes of rice provided by rice suppliers in Denpasar City. Data collectionmethod with survey technique and indepth interview. Data analysis used is descriptiveanalysis, Customer Satisfaction Index and Importance Performance Analysis. Based onthis study the characteristics of the dominating respondents, namely the owner of anelectronic account are women as the couple's head of the family. The high and loweducation does not affect the income they have. Most respondents are from the lowerclass who are registered as KPM and are entitled to rice assistance from the BPNTprogram. Rice endurance is the highest value attribute that is an assessment of consumerpreferences. The satisfaction index of rice BPNT recipients with a total of 80.46% is inthe range of 81% - 100% in the category of very satisfied with some improvementsfrom the results of the IPA method. The results of the Cartesius diagram attribute of riceresistance are the main priority to be improved because it is in quadrant I.